Legal Confıscatıon as a Property Rıght Issue in Turkey - Guloglu, Yavuz (Jurnal Cita Hukum, 2021)
Zoning plans are drawn and written texts prepared as a result of planning activities according to the characteristics of the region in order to meet the social, cultural, human and economic needs of a settlement and to show a safer and more regular development of the place. The property rights of individuals can be restricted by means of the plans prepared by the administration to create livable, orderly and modern living spaces. While the zoning plans are being prepared, the immovables allocated for public services should first be selected from public lands and if these immovables are not sufficient for the places to be allocated to the public service areas, the immovables subject to private property should be allocated to the public service and these areas should be expropriated by the administrations to be allocated on their behalf. The Zoning Law No. 3194 in Turkey is the basic regulation of the zoning law. In the Zoning Law, there is a regulation that the parcels allocated to public services in the zoning plans will be expropriated within five years. However, if the expropriation of the immovables is not completed within the time specified in the legal regulation, the owner who is deprived of his right to dispose of the immovable, is unfairly burdened with a heavy burden. The concept of "legal confiscation" emerges when the property right of the owner of the immovable is restricted for many years only by allocating privately owned immovables to public space in the zoning plans without any actual intervention by the administration. Since the administrations responsible for expropriation mostly avoid this obligation, the procedures established by the administration for planning constitute a disproportionate and unfair intervention in the property rights of the immovable owners. In this study, the definition of the concept of legal confiscation in Turkey, its elements, the remedies for ending the interference with the right to property will be explained, the procedures and principles to be considered during the judgement will be explained by giving examples from the judicial case-law and the decisions of the European Court of Human Rights, and solution proposals will be presented.Keywords: Legal Confiscation; Construction Plan; Property; Contravention Tuntutan Hukum sebagai Permasalah Hak Properti di Turki Abstrak.Undang-undang Zonasi No. 3194 di Turki adalah peraturan dasar dari undang-undang zonasi. Dalam UU Zonasi, ada aturan bahwa persil yang dialokasikan untuk layanan publik dalam rencana zonasi akan diambil alih dalam waktu lima tahun. Akan tetapi, jika pengambilalihan barang-barang tidak bergerak itu tidak selesai dalam waktu yang ditentukan dalam peraturan perundang-undangan, maka pemilik yang dirampas haknya untuk membuang barang-barang tidak bergerak itu, dibebani secara tidak adil dengan beban yang berat. Konsep "sita hukum" muncul ketika hak milik pemilik barang tidak bergerak dibatasi selama bertahun-tahun hanya dengan mengalokasikan barang-barang milik pribadi ke ruang publik dalam rencana zonasi tanpa intervensi nyata dari pemerintah. Karena sebagian besar administrasi yang bertanggung jawab atas pengambilalihan menghindari kewajiban ini, prosedur yang ditetapkan oleh administrasi untuk perencanaan merupakan intervensi yang tidak proporsional dan tidak adil dalam hak milik pemilik tak bergerak. Dalam penelitian ini akan dijelaskan pengertian dari konsep sita hukum di Turki, unsur-unsurnya, upaya penyelesaian untuk mengakhiri campur tangan terhadap hak milik akan dijelaskan, prosedur dan prinsip-prinsip yang harus dipertimbangkan selama penilaian akan dijelaskan dengan memberikan contoh-contoh dari kasus hukum peradilan dan keputusan Pengadilan Hak Asasi Manusia Eropa, dan proposal solusi akan disajikan.Kata Kunci: Penyitaan Hukum; Rencana Pembangunan; Properti; Kontravensi Юридическая конфискация как проблема права собственности в Турции Абстрактный.Закон о зонировании № 3194 в Турции является основным постановлением закона о зонировании. В Законе о зонировании есть положение, согласно которому участки, выделенные для общественных услуг в планах зонирования, будут экспроприированы в течение пяти лет. Однако, если отчуждение недвижимой вещи не завершено в сроки, указанные в правовом регулировании, на собственника, лишенного права распоряжаться недвижимой вещью, несправедливо возлагается тяжелое бремя. Понятие «юридическая конфискация» возникает, когда право собственности владельца недвижимой вещи ограничивается в течение многих лет только путем отнесения частной недвижимой собственности к общественным местам в планах зонирования без какого-либо фактического вмешательства со стороны администрации. Поскольку администрации, ответственные за экспроприацию, в большинстве случаев избегают этого обязательства, процедуры, установленные администрацией для планирования, представляют собой несоразмерное и несправедливое вмешательство в имущественные права владельцев недвижимого имущества. В этом исследовании будет объяснено определение концепции правовой конфискации в Турции, ее элементы, средства правовой защиты для прекращения вмешательства в право собственности, а также будут объяснены процедуры и принципы, которые должны быть рассмотрены в ходе судебного решения, с помощью примеров из будет представлена судебная практика и решения Европейского суда по правам человека, а также предложения по их решениям.Ключевые слова: Конфискация; План Строительства; Собственность; Правонарушение